Effectiveness of Cognitive-Attribution Therapy on Shame and Guilt Feelings of Women Exposed to Spousal Rejection in Nigeria - Shobola, Adeola (Richtmann Publishing, 2013)
Nowadays, one of the ways to reject a woman in Africa especially Nigeria is when the spouse elopes with a lady in theWestern state in the guise of seeking greener pastures. Economic depression, lack of job and general insecurity, politicalinstability and lack of social amenities have been attributed to reasons many men leave their home country for the Westernworld for better living for self and the family; but the current trend has been abandon, neglect and eventual divorce of thewomen with their children. This has brought shame and guilt to many women because of the perception of many Africanstowards divorce. This empirical study involved twenty-five women whose husbands have been overseas in the last five to tenyears and waiting to be invited over; but were later divorced. It was established that these women were suffering from guilt andshame. The twenty-five volunteer women were subjected to twelve weeks counseling using self-developed scales that werepatterned after Cognitive-Attribution Therapy of Lewis (1993), and Shame and Guilt of Barrett (1995). The prognosis revealedthat the level of shame and guilt of the women were reduced; some of them concluded to move forward by remarrying, whileothers concluded to take the incidence as fate and continue to take care of self and children. It was concluded that manypeople inflict self pain on self for not being responsible for a particular occurrence, but psychological therapies such asCognitive-Attribution can be applied to help such individuals.